2017
DOI: 10.1016/j.wjorl.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of sinonasal inverted papilloma: A narrative review

Abstract: ObjectiveSinonasal inverted papilloma (IP) is a benign and uncommon tumor of the nasal cavity and paranasal sinuses with a tendency for recurrence and even malignant transformation. Though the morphology and clinical behavior of this lesion has been well described, its etiology remains controversial.MethodsComputerized searches were performed in PubMed, Scopus, and Google scholar through May 2015. In this review, etiologic factors including human papilloma virus (HPV), Epstein–Barr virus (EBV), cell cycle rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
1
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 36 publications
2
76
1
12
Order By: Relevance
“…5,7 In addition, Yoon et al 7 found that 21.9% of IPs were immediately adjacent to inflammatory polyps suggesting that chronic inflammation is associated with IP. 8 Orlandi et al 6 found that patients with IP tended to have higher Lund-Mackay scores on the contralateral side; however, this was not found to be statistically significant.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…5,7 In addition, Yoon et al 7 found that 21.9% of IPs were immediately adjacent to inflammatory polyps suggesting that chronic inflammation is associated with IP. 8 Orlandi et al 6 found that patients with IP tended to have higher Lund-Mackay scores on the contralateral side; however, this was not found to be statistically significant.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, Yoon et al . found that 21.9% of IPs were immediately adjacent to inflammatory polyps suggesting that chronic inflammation is associated with IP . Orlandi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Many authors studied the implication of Human Papilloma Virus (HPV) in the etiology of IP, but the data found in the literature are still contradictory. Different meta-analyses show that HPV rates between 17-38% 10 , 6 and 11 serotypes being associated with the benign form of IP, while 16 and 18 serotypes are related to malignancy [19][20][21][22] . There are also authors who do not sup-port this theory 19,23,24 .…”
Section: Incidence and Etiopathogenesismentioning
confidence: 99%
“…Different meta-analyses show that HPV rates between 17-38% 10 , 6 and 11 serotypes being associated with the benign form of IP, while 16 and 18 serotypes are related to malignancy [19][20][21][22] . There are also authors who do not sup-port this theory 19,23,24 . A recently published study from Mohajeri et al 25 does not support the role the human papilloma virus plays as an etiological factor for disease recurrence or its potential progression to squamous cell carcinoma.…”
Section: Incidence and Etiopathogenesismentioning
confidence: 99%
See 1 more Smart Citation